Evolution of patients with squamous cell carcinoma of upper aerodigestive tract - Ali Amar; Sergio Altino Franzi; Abrão Rapoport (São Paulo Medical Journal)
CONTEXT: Local and regional recurrences are frequent in patients with squamous cell carcinoma of the upper aerodigestive tract and early diagnosis is important for salvage treatment. OBJECTIVE: To identify the period of highest risk for the development of recurrences after surgical treatment of squamous cell carcinoma of the upper aerodigestive tract, in spite of radical therapy, in order to plan the follow-up for these patients. TYPE OF STUDY: Cross-sectional, descriptive. SETTING: Department of Head and Neck Surgery/Otorhinolaryngology, Heliópolis Hospital (Hosphel), São Paulo, Brazil. PARTICIPANTS: A review was made of the hospital records of 889 patients with squamous cell carcinoma of the upper aerodigestive tract surgically treated between October 1977 and December 1996: 364 had oral cavity tumors, 107 had tumors of the oropharynx, 152 of the hypopharynx and 266, larynx tumors. The disease was stage I in 14 patients, stage II in 117, stage III in 352, stage IV in 397 and 9 patients were not staged. MAIN MEASUREMENTS: The interval between treatment and recurrence of disease was evaluated. The results were expressed as medians, quartiles (25% to 75%) and percentiles (10% to 90%). The annual incidence of recurrences and second tumors was calculated. RESULTS: Seventy-four percent of the recurrences were diagnosed within 18 months post-treatment. The local and regional recurrences and distant metastases showed medians of 270, 210 and 435 postoperative days respectively. The incidence of a second primary tumor varied from 2 to 3.1% a year. CONCLUSION: The majority of recurrences occurred within 18 months after the initial surgical treatment. The incidence of a second tumor remained stable after the first post-treatment year.